2018
DOI: 10.1097/scs.0000000000005056
|View full text |Cite
|
Sign up to set email alerts
|

Objectifying Micrognathia Using Three-Dimensional Photogrammetric Analysis

Abstract: Background: Micrognathia occurs isolated and as part of entities like Robin sequence (RS). An objective measurement of mandible size and growth is needed to determine the degree of micrognathia and enable a comparison of treatment outcomes. We undertook a pilot study to investigate the usability of 3D facial photogrammetry, a fast, non-invasive method, to estimate mandible size and growth in a small cohort of newborns and infants. Methods: We estimated exterior mandibular volume using a tetrahedron defined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…From a study of children recruited with and without PAE, we show here that several SNPs in BMPR1B are significantly associated with ethanol- associated jaw malformations. Jaw hypoplasia is commonly observed in FASD (6,7,69) but studying FASD in humans is incredibly challenging due to the complex interplay between genetic background and ethanol timing and dosage. Our results show that zebrafish analyses can model gene-ethanol associations in humans, strongly phenocopying both the malformation and the variation inherent in human data (7,11,70).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a study of children recruited with and without PAE, we show here that several SNPs in BMPR1B are significantly associated with ethanol- associated jaw malformations. Jaw hypoplasia is commonly observed in FASD (6,7,69) but studying FASD in humans is incredibly challenging due to the complex interplay between genetic background and ethanol timing and dosage. Our results show that zebrafish analyses can model gene-ethanol associations in humans, strongly phenocopying both the malformation and the variation inherent in human data (7,11,70).…”
Section: Discussionmentioning
confidence: 99%
“…DSMs allow us to compute facial signatures, which represent normalized differences between groups, and visualize using a heatmap representation group or individual differences (85). To evaluate micrognathia, we computed mandible volume, which was outlined and validated against CT images in (69). This technique estimated the volume of a trapezoid formed by four specific points on the size- normalized face: the left and right lower otobasion inferius (lowest points of the ears), gnathion (tip of the mandible), and lower lip vermillion center (Supplement Fig.…”
Section: Methodsmentioning
confidence: 99%
“…After further assessment 7 articles were included to answer the second research question of this chapter. Of these, 4 studies addressed micrognathia: a retrospective cohort study by Gao et al (2019), a pilot study by Basart et al (2018) and 2 prospective cohort studies by Mermans et al (2020) and Mimouni et al (2020). [15][16][17][18] Glossoptosis was discussed in 3 studies: a retrospective study by Lee et al (2018) and 2 prospective cohort studies by 2018).…”
Section: Literature Searchmentioning
confidence: 99%
“…The use of 3 dimensional (3D) photogrammetric analysis is studied by Basart et al (2018). 16 4 isolated RS patients and 8 nonisolated RS patients were included.…”
Section: Diagnosing Micrognathiamentioning
confidence: 99%
“…3D facial measurements of the normal and micrognathic infant are available using 3D surface scanners [9,10]. A recent study showed good correlation between surface measurements and interior mandibular volume [11].…”
Section: Introductionmentioning
confidence: 99%